(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of carotid artery stenosis in ischemic stroke patients at a teaching hospital. Study design: It’s a cross-sectional study. Settings: Department of Diagnostic Radiology Combined Military Hospital (CMH), Lahore from October 2024 to May 2025. Methodology: A total of 185 ischemic stroke patients aged 18–60 years were recruited using non-probability consecutive sampling. Carotid artery stenosis was assessed via Doppler ultrasound using NASCET criteria. Severity was classified as mild, moderate, severe, or total occlusion. Results: Among 185 ischemic stroke patients, 84.3% had carotid artery stenosis as detected by Doppler ultrasound. Moderate stenosis (50–69%) was most common, followed by mild, severe, and total occlusion. Smoking was significantly associated with CAS (p = 0.026). Age, BMI, hypertension, and diabetes showed no statistically significant association. Conclusion: Carotid artery stenosis was highly prevalent among ischemic stroke patients in this study. Routine Doppler screening is crucial for early detection, especially in high-risk individuals. Preventive strategies targeting modifiable risk factors like smoking are essential.